Workspace Analysis of a Mobile Manipulator with Obstacle Avoidance in 3D Printing Tasks - Robert Guamán Rivera; Rodrigo García Alvarado; Alejandro Martínez-Rocamora; Fernando Auat Cheein (Applied Sciences, 2021)
The knowledge of the workspace for a robotic system on construction sites represents an essential resource to ensure the work progress, guarantee the safety of the construction tasks, and avoid robot damage. Despite the dramatic development of 3D printing technologies with robotic systems in recent years, these are still several challenges to consider, such as the size of the printing profile and obstacles in the construction site. This work presents the results from evaluating the workspace of a mobile manipulator in 3D printing tasks on construction sites. The methodology analyses the printing workspace based on the workspace of the mobile manipulator, considering fixed obstacles and possible collisions between the robot and obstacles during 3D printing tasks. The results showed that the shape of the printing profile defined as a building element changes the shape of the printing workspace. Furthermore, the obstacles in the construction site and height variation of the printing profile cause changes in the displacement of the robotic platform and values of rotation of its joints, which also modify the shape of the printing workspace.